Diseño de sistema domótico estandarizado para el control de los sistemas de iluminación, climatización, proyeccion multimedia, seguridad y rollers motorizados en un local de coworking - Cruzado Vargas, Josue Gabriel (2019)
The objective of this project was to design a home automation system to control the different systems of a commercial premises using a standardized home automation protocol, for this a coworking room was chosen in the city of Trujillo, the coworking site chosen was "Estación Coworking" located in “San Andrés - Trujillo”, which is a three-story store with seven offices and different environments of common use. The systems to be controlled in Coworking Station are the lighting, air conditioning, multimedia and security systems. For this purpose, a standardized home automation protocol was used, choosing the most appropriate for the design through a comparative evaluation between different existing protocols in the market. Finally, it was possible to carry out the complete design of a domotic system that controls all the existing systems in the premises in question. One of the most important results was the development of a pioneering model for the design of domotic systems in the city of Trujillo.